Inhibition of endogenous thioredoxin-1 in the heart of transgenic mice does not confer cardioprotection in ischemic postconditioning. (December 2016) - Perez, Virginia; D′ Annunzio, Verónica; Mazo, Tamara; Marchini, Timoteo; Caceres, Lourdes; Evelson, Pablo; Gelpi, Ricardo J.
Abstract: Thioredoxin-1 maintains the cellular redox status and decreases the infarct size in ischemia/reperfusion injury. However, whether the increase of thioredoxin-1 expression or its lack of activity modifies the protection conferred by ischemic postconditioning has not been yet elucidated. The aim was to evaluate if the thioredoxin-1 overexpression enhances the posctconditioning protective effect, and whether the lack of the activity abolishes the reduction of the infarct size. Wild type mice hearts, transgenic mice hearts overexpressing thioredoxin-1, and a dominant negative mutant (C32S/C35S) of thioredoxin-1 were used. The hearts were subjected to 30 min of ischemia and 120 min of reperfusion (Langendorff) (I/R group) or to postconditioning protocol (PostC group). The infarct size in the Wt-PostC group decreased in comparison to the Wt-I/R group (54.6 ± 2.4 vs. 39.2 ± 2.1%, p < 0.05), but this protection was abolished in DN-Trx1-PostC group (49.7 ± 1.1%). The ischemia/reperfusion and postconditioning in mice overexpressing thioredoxin-1 reduced infarct size at the same magnitude (35.9 ± 2.1 and 38.4 ± 1.3%, p < 0.05 vs. Wt-I/R). In Wt-PostC, Trx1-I/R and Trx1- PostC, Akt and GSK3β phosphorylation increased compared to Wt-I/R, without changes in DN-Trx1 groups. In conclusion, given that the cardioprotection conferred by thioredoxin-1 overexpression and postconditioning, is accomplished through the activation of the Akt/GSK3β survival pathway, no synergic effect was evidenced. Thioredoxin-1 plays a key role in the postconditioning, given that when this protein is inactive the cardioprotective mechanism was abolished. Thus, diverse comorbidities or situations modifying the thioredoxin activity, could explain the absence of this strong mechanism of protection in different clinical situations.